TROUBLES IN TEACHING THE RUSSIAN LANGUAGE TO PRIMARY SCHOOL PUPILS - Niyazova Kh. Kh. (Modern American Journals, 2025)
The article discusses the challenges of teaching Russian to elementary school students at the beginning of their education. The following can be stated in accordance with the sound analytical-synthetic method's tenets, which guarantee the efficacy of writing and reading by observing their unity: utilizing the age-related psychological traits of schoolchildren to create an environment that encourages pupils' engagement in language subjects and their comprehension of their value.
Keywords: Russian language, reading and writing abilities, learning a native tongue, Russian language learning strategy, primary school.